Light in August - Faulkner, William, 1897-1962. (New York : Vintage Books, 1990)
Published in 1932, Light in August is the seventh in the series of William Faulkner's novels set in the fictional Yoknapatawpha County, Mississippi. The book tells the story of the orphan Joe Christmas, whose mixed black-white heritage condemns him to life as an outsider who is hated by some and pitied by others.
Originally published: Harrison Smith and Robert Haas, 1932.
"This revised text and the notes are reprinted from Novels 1930-1935 by William Faulkner, published by the Library of America, 1985, by permission"--T.p. verso.
Accelerated Reader AR
Keywords: Racially mixed people -- Fiction; Pregnant women -- Fiction; Drifters -- Fiction; Mississippi -- Fiction; Allegories; Stream of consciousness fiction